Exploring Cultural Difference Through Translating Children’s Literature - Metcalf, Eva-Maria (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2003)
AbstractThis article is descriptive in nature, presenting a student-faculty project in which participants translated a short children’s story from German into English in order to explore the cultural embeddedness of language and the hermeneutic nature of translation. By reflecting on issues surrounding the translation of children’s literature and by imitating the situation of a professional translator, project participants gained insight into the workings of language and the complexities associated with translation.